Toward a pragmatist philosophy of the humanities - Pihlström, Sami (Albany : State University of New York Press, 2022)
"Humanist scholars often feel the need to defend the humanities. The value of humanistic research is sometimes challenged, as the cultural "reality" investigated by disciplines such as history, literary studies, and theology may seem unclearIn particular, the ontology of the humanities might be considered obscure in comparison to the ontology of the natural sciences. Toward a Pragmatist Philosophy of the Humanities proposes to develop a comprehensive philosophical account of the humanities, focusing on the ontology and epistemology of humanistic inquiry from the standpoint of pragmatism. Sami Pihlström argues that humanistic cognitive pursuits can be interpreted along the lines of a pragmatist theory of inquiry, defending pragmatic realism about the humanities. However, far from leading to any reductive naturalization of the human world, the pragmatist philosophy of the humanities defended by Pihlström takes a distinctively Kantian critical turn in emphasizing the need for transcendental argumentation in the philosophy of the humanities, insisting on the irreducibly ethical dimensions of humanistic scholarship"--
1. Introduction : Why this book? -- 2. Realism, practices, and inquiry : What is pragmatist philosophy of the humanities? -- 3. Developing pragmatist philosophy of literary theory, historiography, and religious studies -- 4. Pragmatic naturalism and transcendental arguments in the philosophy of the humanities -- 5. Conclusion : The values and limits of the humanities.
Includes bibliographical references and index.
Sami Pihlström is Professor of Philosophy of Religion at the University of Helsinki in Finland.
Print version record.
JSTOR
Keywords: Humanities -- Philosophy; Pragmatism; History -- Philosophy; Literature -- Philosophy; Religion -- Philosophy; Pragmatisme; Histoire -- Philosophie; Religion -- Philosophie; pragmatism; PHILOSOPHY / Movements / Pragmatism; History -- Philosophy; Humanities -- Philosophy; Literature -- Philosophy; Pragmatism; Religion -- Philosophy